Pengaruh Pendidikan Keuangan Di Keluarga Dan Teman Sebaya Terhadap Perencanaan Keuangan Pribadi - Farhan Rizqullah, Muhammad; Andayani, Sari (Fakultas Ekonomi Universitas Gresik, 2023)
The purpose of this study was to test and prove the effect of financial education in family and peers on personal financial planning. This research applies a